Corneal Epithelial Toxicity after Intravitreal Methotrexate Injection for Vitreoretinal Lymphoma: Clinical and In Vitro Studies - Jeong, Yoon (J Clin Med, 2020)
Methotrexate is widely used as an intraocular chemotherapy for vitreoretinal lymphoma (VRL). Although corneal toxicity has been reported in patients after intravitreal methotrexate injections, the incidence, outcome, and mechanism of the toxicity are unclear. Herein, we performed a clinical study to evaluate the incidence, predisposing factors, and treatment outcome of corneal epitheliopathy associated with intravitreal methotrexate injection. In addition, we directly investigated cytotoxic effects and mechanisms of methotrexate in cultures of human corneal epithelial cells (CECs). Medical chart reviews revealed that corneal epitheliopathy occurred in 15 eyes (22.7%, 12 patients) out of 66 eyes (45 patients) after intravitreal methotrexate injections for treatment of VRL. The use of topical anti-glaucoma medication was significantly associated with development of corneal epitheliopathy. The epitheliopathy resolved in all patients 2.4 months after onset. In culture, methotrexate decreased the survival of CECs by inducing apoptosis, increasing oxidative stress, suppressing proliferation, and upregulating inflammatory cytokines. The addition of folinic acid significantly protected the cells from the methotrexate-induced toxicity. Hence, our results suggest that care should be taken to minimize the contact of methotrexate with corneal epithelium during injection, and folic or folinic acid supplementation might be beneficial for preventing corneal complications in patients undergoing intravitreal methotrexate injections.